Risk of seizure recurrence in people with single seizures and early epilepsy – Model development and external validation. (January 2022) - Bonnett, Laura J.; Kim, Lois; Johnson, Anthony; Sander, Josemir W.; Lawn, Nicholas; Beghi, Ettore; Leone, Maurizio; Marson, Anthony G.
Highlights: Model predicts risk of seizure recurrence after single fit or epilepsy diagnosis. Model performs well in independent data. Future work required to ensure the model is adopted in clinical practice. Model can improve the lives of people with single seizures and early epilepsy. Abstract: Purpose: Following a single seizure, or recent epilepsy diagnosis, it is difficult to balance risk of medication side effects with the potential to prevent seizure recurrence. A prediction model was developed and validated enabling risk stratification which in turn informs treatment decisions and individualises counselling. Methods: Data from a randomised controlled trial was used to develop a prediction model for risk of seizure recurrence following a first seizure or diagnosis of epilepsy. Time-to-event data was modelled via Cox's proportional hazards regression. Model validity was assessed via discrimination and calibration using the original dataset and also using three external datasets – National General Practice Survey of Epilepsy (NGPSE), Western Australian first seizure database (WA) and FIRST (Italian dataset of people with first tonic-clonic seizures). Results: People with neurological deficit, focal seizures, abnormal EEG, not indicated for CT/MRI scan, or not immediately treated have a significantly higher risk of seizure recurrence. Discrimination was fair and consistent across the datasets (c-statistics: 0.555 (NGPSE); 0.558 (WA); 0.597 (FIRST)). Calibration plots showed good agreement between observed and predicted probabilities in NGPSE at one and three years. Plots for WA and FIRST showed poorer agreement with the model underpredicting risk in WA, and over-predicting in FIRST. This was resolved following model recalibration. Conclusion: The model performs well in independent data especially when recalibrated. It should now be used in clinical practice as it can improve the lives of people with single seizures and early epilepsy by enabling targeted treatment choices and more informed patient counselling.